Physiological and Biochemical Responses in the Blood of Striped Catfish (Pangasianodon hypophthalmus) to the Addition of Papaya Seed Extract (Carica papaya L.) to Feed - Dimas Gasliani Akbar; Henni Syawal; Morina Riauwaty (Jurnal Perikanan dan Kelautan, 2026)
Striped catfish (Pangasianodon hypopthalmus) is a group of catfish that has become one of the leading freshwater commodities. This gives striped catfish (P. hypopthalmus) a fairly good market potential. A frequent constraint in fish farming is the risk of disease outbreaks. One factor contributing to the failure of fish farming and resulting in significant mortality is disease. One pathogenic bacterium responsible for disease is Aeromonas hydrophila, which is often found in freshwater and causes 80-100% of fish mortality in a short period. The method used is an experimental method employing a Completely Randomized Design (CRD) with one factor, 5 treatment levels, and 3 replications. The treatments used in this study refer to. The study on the addition of papaya seed extract (Carica papaya L.) to the feed found that it affects the physiological and biochemical responses of striped catfish (P. hypophthalmus). The best feeding dosage with the addition of papaya seed extract of 3.0 mL/kg of feed results in glucose levels of 70.33 mg/dL, calcium 12.53 mg/dL, magnesium 2.73 mg/dL, phosphorus 8.66 mg/dL, lysozyme activity 275 units/mL, absolute weight gain 14.92g, absolute length gains 5.25cm, and survival rate reaching 93.33%. The researcher recommends conducting further studies on the addition of papaya seed extract at a dosage of 3.0 mL/kg of feed to improve growth in different test fish and advises against using papaya seed extract in high doses.